Pengaruh Service Quality, Price dan Service Value Terhadap Kepuasan Pelanggan Pada New Melati Salon Denpasar-Bali - Desianti, Ni Nyoman Putri; Seminari, Ni Ketut (E-Jurnal Manajemen, 2014)
The development of a beauty salon in Indonesia and the world is growing rapidly. An increasing number of beauty salons that are currently able to be used as one indicator of the growing interest of consumers to look fresh and healthy. New Jasmine is one of the beauty salon company service providers are already widely known in the city of Denpasar. In an effort to retain customers, companies need to strive to create customer satisfaction. A satisfaction obtained through a number of factors some of which are quality of service, price and value of service. 127 respondents were sampled, using a non-probability sampling method with purposive sampling method. Data collected through questionnaires, observation  and interviews. Testing in this study using the technique of multiple linear regression analysis. Should still consider the price of the salon with the appropriate quality of service provision. Key words: service quality, price and service value